Requisitos e arquiteturas das redes de telefonia móvel de quinta geração - Oliveira, Gabrielli Mariana de [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Mobile communications have a trajectory defined by exponencial advancement, compared to emerging technologies that are constantly emerging. Although some regions still do not have it in place, 4G, as fifth generation networks, have already been mapped and designed to meet the high market demand connectivity. The main objective of lhe work is to present an in-depth analysis of 5G networks, starting from lhe requirements and specifications expected for the system and covering ali emerging technologies that were allocated to structure the network architecture of this generation. We propose, therefore, a brief study of possible cases of use and deployments when integrated into scenarios where mobile communication goes beyond telephony and Internet access, describing services specific to certain market sectors. From this perspective, a generalized perspective on the insertion of 5G in the Brazilian market is defined to illustrate and point out the challenges faced by operators facing the 5G auction and the integration of the network throughout the Brazilian territory. The final analysis will be given towards possible future plans both for the definition of a next generation, and for implementing and achieving ali the expected requirements of 5G.

As comunicações móveis tem uma trajetória definida pelo avanço exponencial, frente às tecnologias emergentes que surgem constantemente. Apesar de algumas regiões ainda não possuir de forma concretizada, o 4G, as redes de quinta geração já foram mapeadas e projetadas para atender a alta demanda do mercado. O objetivo central do trabalho é apresentar uma análise aprofundada das redes 5G, partindo dos requisitos e especificações esperados para o sistema e percorrendo todas as tecnologias emergentes que foram alocadas para estruturar a arquitetura de rede desta geração. Propõe-se, assim, um breve estudo dos possíveis casos de uso e de implantações quando integrados à cenários onde a comunicação móvel vai além da telefonia e do acesso à Internet, descrevendo serviços específicos à determinados setores do mercado. Sob essa ótica, uma perspectiva generalizada sobre a inserção do 5G no mercado do Brasil é definida para ilustrar e apontar os desafios encontrados pelas operadoras frente ao leilão 5G e a integração da rede em todo o território brasileiro. A análise final será dado em entender os possíveis planos futuros tanto para a definição de uma próxima geração, quanto para efetivar e atingir todos os requisitos esperados do 5G.
Requirements and architectures of fifth generation mobile telephony networks
Keywords: Internet; Sistemas de telefonia celular; Telecomunicações; Telefonia celular